Modeling and optimization : theory and applications : MOPTA, Bethlehem, PA, USA, August 2017, Selected contributions /: theory and applications : MOPTA, Bethlehem, PA, USA, August 2017, Selected contributions. (2019) - Unknown
No abstract available